Observatorio de Costes y Financiación del Transporte Urbano Colectivo: Un programa de investigación - Daniel Sánchez Toledano; Daniel Carrasco Díaz; Joaquín Sánchez Toledano (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2014)
– The Observatorio de Costes y Financiación del Transporte Urbano Colectivo (Cost and Funding of Urban Transport Watchdog) and its annual reports on this industry provide an excellent platform to improve awareness of its cost structure, to enable benchmarking strategies/practices for companies, and to fund policies for an efficient public service. Alongside this, setting-up a database which includes a battery/series of comprehensive and core parameters for studying the conditions of public service provision in Spain, is a first-order information base that must be used to generate industry knowledge and develop multiple lines of research to be explored in the future. In this paper we aim to present a potential research roadmap in this area.
Keywords: 330; Costs; Transport; Efficiency; Funding; Data mining